Trastuzumab and ECG Changes Dilemma - Azin Alizadehasl; Mina Mohseni; Feridoun Noohi Bezanjani; Majid Maleki; Kamran Roudini (International Journal of Hematology-Oncology and Stem Cell Research, 2023)
Trastuzumab and ECG changes dilemma